The Influence of Tax Understanding, Service Quality, and Tax Sanctions on the Compliance of Land and Building Tax (PBB-P2) Taxpayers in Cirebon Regency - Safitri Ratna Komala; Rinni Indriyani; Fitriya Sari (International Journal of Economics and Management Research, 2024)
This study aims to analyze the influence of taxpayer understanding, service quality, and tax sanctions on taxpayer compliance in paying Rural and Urban Land and Building Tax (PBB-P2) in Cirebon Regency. A quantitative approach was employed through a survey method by distributing questionnaires to 100 individual taxpayers. The data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that, both partially and simultaneously, all three independent variables have a positive and significant effect on taxpayer compliance. A good understanding of taxation, high-quality fiscal services, and the implementation of fair and firm tax sanctions enhance public awareness and compliance in fulfilling tax obligations. The coefficient of determination (Adjusted R²) value of 0.726 suggests that these three variables explain 72.6% of the variation in taxpayer compliance, while the remaining 27.4% is influenced by other variables outside the scope of this study. These findings offer practical implications for local governments and tax authorities to continuously improve tax education, public services, and consistent law enforcement to optimize regional tax revenue.